Javelin performance prediction test - Gorski, J.
1) Backward overhead shot. (16 lb for men/4kg for women) Throw from on a shot toeboard into shot landing area; measure as a normal shot competition. Scoring values- 40'= 600pts 45'=720 50'=840 55'=960 60'=1080 65'=1200 add/subtract 2 pts/ inch. 2) Standing long jump. Jump from edge of LJ landing pit; toes are allowed to hang over edge to give some leverage. Measure from heel landing to pit edge. Scoring values- 7'= 840pts 8'= 960 9'= 1080 10'= 1200 add/subtract 10 pts/ inch. 3) Standing triple jump. This is to simulate the last 3 steps of the throw; L-R-L for a right hand thrower. Start w/ rt. foot forward (fig 1) and step into left foot jump (fig 2), then right foot jump (fig 3) then final left foot jump (fig4) to a double foot landing (fig 5). This is done off a LJ runway into a sand landing area and measured from heel landing to toe of left foot takeoff. Scoring values- 27'=486pts 28'=504 29'=522 30'=540 31'=558 add/subtract 3 pts/inch. 4) 2-hand overhead shot. (4kg for men/3kg for women) Throw from on a shot toeboard into shot landing area. Arch back as far as possible (fig 6) and deliver shot w/ both hands in a soccer style throw(fig 7); measure as a normal shot competition. Scoring values- 45'=540 pts 50'=600 55'=660 60'=720 65'=780 add/subtract 2 pts/inch 5) 3 step 600/400 gm ball throw. Throw from javelin runway or on track; start with right foot in front(for right hand thrower) and step 1 is onto left foot, then normal crossover and plant to deliver ball from behind foul line. Stepping over the foul line is allowed; measure throw as in normal javelin competition. Scoring values- 190'=390pts 200'=405 210'= 418 220'=443 230'=458 240'=476 add/subtract 1 pt/8 inches 6) 30m crossovers. Done with javelin in hand on the track. Stopwatch started at first movement (indicated by official at starting point) of the athlete. Timed to the 1/10 second. Scoring values- 4.0=740pts 4.2=720 4.4=700 4.6=680 4.8=660 5.0=640 add/subtract 10 pts/.1 seconds 7) Back arch. Anchor toes against a firm edge so they don't slide. Arch up into hands and toes support (fig 8) and walk hands in towards heels as close as possible while keeping hips up as high as possible. Measure from finger tips to toe anchor. Scoring values- 40cm=995pts 50cm=895 60cm=795 70cm=695 80cm=595 add/subtract 10 pts/1 cm 8) Standing throw position. This test is a bit subjective in evaluation. The athlete assumes a good delivery position, trying to get into the "bow" position that they would from running into the plant (fig 9). The "official" looks for good position as it simulates the actual throw, not just reaching the throwing hand back close to the back foot. Measure from ground to the throwing wrist. Scoring values- 60cm=1120pts 70cm=1050 80cm=980 90cm= 910 100cm=640 add/subtract 7 pts/1 cm 9) Shoulder roll w/ javelin. Standing with javelin held at arms length (fig 10), pass the javelin overhead (fig 11) and behind the back (fig 12), then return to start. Keep the elbows locked and both hands pass overhead together; don't let one hand go over then the other. Measure distance between the index finger knuckles. Scoring values- 40cm= 995pts 50cm=895 60cm=795 70cm=695 80cm=595 add/subtract 10 pts/1 cm